ENCLOSURE SIZE OF ANIMALS OF LAHORE ZOOLOGICAL GARDEN IN COMPARISON OF INTERNATIONAL NORMS - Z. Hussain; Z. Ali; A. Nemat; S. Ahmad; S. K. Sikander; Kiran Saleem (Journal of Animal and Plant Sciences, 2015)
The study was conducted in Lahore zoological gardens regarding the enclosure sizes of animals and birds to check that whether the sizes of the enclosures meet the international standardfor enclosure sizes or not.Lahore zoo was established in 1872, it holds a number of exotic, endogenous and endangered species. The sizes of enclosures were compared with the standards of AZA, CZA, IWRC and NWRA.The study population comprises of 95 species of animals and birds with total number of individuals 521. Out of 11 species of mammals compared,the enclosure sizes of 7 were appropriate, out of 16 species of herbivores, 8 were having sufficient enclosure sizes, 6 species of primates were present out of which only 4 were having appropriate cage sizes, out of 10 species of reptiles the enclosure sizes of only 3 were appropriate. Out of 45 kinds of birds (38 species) the cage sizes of only 13 were appropriate, while all running birds and water birds were having sufficient enclosure sizes. It was concluded that at Lahore zoological gardens, 45% enclosures meet international standards and had area sufficient for the animals, while the rest needs to be provided with more area. Abbreviations: AZA: Association of Zoo and Aquarium, CZA: Central Zoo Authority, EAZA: European Association of Zoos and Aquaria, IWRC: International Wildlife Rehabilitation Council, NWRA: National Wildlife Refuge Association space for normal movement of an animal, such as
Keywords: Lahore Zoo; Enclosure Size; International Zoo rules